Intellectual-Social Dynamics at State Islamic University in Indonesia: The Role of Alumni of Islamic Boarding Schools from Bangka Island - Sulaiman, Rusydi; Yanasari, Pebri (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This article aims to sense the intellectual and social dynamics of alums of Islamic boarding schools or the pesantren from Bangka Island and their role in State Islamic University, PTKIN in Indonesia. These issues are analyzed with Linton's role theory. This qualitative research takes primary data from eight informants, while secondary data is taken from other informants as an addition. The data was collected through observation, semi-structured interviews, and documentation. The